2007
DOI: 10.1148/radiol.2433060157
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Radiofrequency Ablation of Hepatic Tumors against the Diaphragm: Frequency of Diaphragmatic Injury1

Abstract: Of 29 patients who had ablation of hepatic tumors adjacent to the diaphragm, five (17%) had diaphragmatic injury, which was clinically apparent with right shoulder pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 32 publications
4
59
2
1
Order By: Relevance
“…However, our raw data of 24% of peridiaphragmatic RFA patients with right shoulder pain versus 5% in RFA elsewhere, does demonstrate a trend. Our reported 24% with right shoulder pain is similar to data from Kang, et al but is greater than in Head, et al [7]. This increased rate of shoulder pain in the peridiaphragmatic RFA group could be secondary to inflammation of the diaphragm from RFA, causing associated phrenic nerve irritation.…”
Section: Painsupporting
confidence: 87%
See 2 more Smart Citations
“…However, our raw data of 24% of peridiaphragmatic RFA patients with right shoulder pain versus 5% in RFA elsewhere, does demonstrate a trend. Our reported 24% with right shoulder pain is similar to data from Kang, et al but is greater than in Head, et al [7]. This increased rate of shoulder pain in the peridiaphragmatic RFA group could be secondary to inflammation of the diaphragm from RFA, causing associated phrenic nerve irritation.…”
Section: Painsupporting
confidence: 87%
“…This is an extremely low mortality rate that is comparable to overall hepatic tumor RFA periprocedural reported mortality of <0.5% [43]. Also, previous review of literature reports a rate of diaphragmatic injury in only 0.16% (6/3670) of all hepatic tumor RFA cases [7], [19]. Reports of major complication associated with RFA of peridiaphragmatic HCC lesions demonstrate a wide range from 0% -45% and complications included mostly reports of pneumothoraces and pleural effusions [26], [36], [44]- [46].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…It has also proven efficacious in the treatment of recurrent HCC lesions following partial hepatectomy [35,41] . It should however, be avoided in case of lesions located in the dome or the inferior edge of the liver due to the risk of diaphragmatic injury [42] . It is also advisable to avoid RFA in case of sub-capsular tumors located within 1 cm of the hepatic capsule, due to the risk of needle-track seeding, which was observed in 4 out of 32 patients in a series [43] [ Table 1].…”
Section: Rfamentioning
confidence: 99%
“…However, Head HW et al reported that 5 (17%) in 29 radiofrequency ablation cases of hepatocellular carcinoma adjacent to the diaphragm had right shoulder pain and 3 cases showed thickening of the diaphragm induced by the thermal effect of radiofrequency ablation (Head et al, 2007). It is also reported that the symptom of diaphragm injury manifests as referred right shoulder pain that occurs during the treatment and can last up to 2 weeks after the ablation (Livraghi et al, 2003).…”
Section: Reported Complications Including a Diaphragmatic Hernia In Tmentioning
confidence: 99%